Positive electrode active material, its manufacturing method, and positive electrode and lithium secondary battery including the same
Patent Information
- Application Number
- JP2023550303
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-05
- Filing Date
- 2022-03-04
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-03-04
AI Technical Summary
【0013】 TiおよびBを特定の含量で含む本発明による正極活物質は、低い充電状態(SOC)および低温で優れた出力特性を維持することができる。したがって、低い充電状態と低温で高い出力特性が求められる電気自動車用二次電池に有用に使用されることができる。
Smart Images

Figure 0007643801000002 
Figure 0007643801000001
Abstract
Description
Technical Field
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0029597 filed on March 5, 2021, and all the contents disclosed in the document of the Korean patent application are incorporated herein by reference in their entirety.
[0002] The present invention relates to a positive electrode active material, a method for manufacturing the same, a positive electrode including the same, and a lithium secondary battery. More specifically, the present invention relates to a positive electrode active material with improved normal temperature and low temperature output characteristics, a method for manufacturing the same, a positive electrode including the same, and a lithium secondary battery.
Background Art
[0003] Recently, with the development of technologies related to mobile devices and electric vehicles and the increasing demand, the demand for secondary batteries as an energy source has been rapidly increasing. Among such secondary batteries, lithium secondary batteries having high energy density, high voltage, long cycle life, and low self-discharge rate have been commercialized and widely used.
[0004] As positive electrode active materials for lithium secondary batteries, lithium transition metal oxides such as lithium cobalt oxides such as LiCoO2, lithium nickel oxides such as LiNiO2, lithium manganese oxides such as LiMnO2 or LiMn2O4, and lithium iron phosphate compounds such as LiFePO4 have been developed. Recently, Li[Ni p Co q Mn r O2, Li[Ni p Co q Al r O2, Li[Ni p Co q Mn r Al s O2 (where 0 < p < 1, 0 < q < 1, 0 < r < 1, 0 < s < 1), lithium composite transition metal oxides containing two or more transition metals have been developed and widely used.
[0005] Meanwhile, with the recent increase in demand for high-capacity batteries to be used in electric vehicles, etc., active development is underway on high-nickel (High-Ni) positive electrode active materials, which have improved capacity characteristics by increasing the nickel content in lithium composite transition metal oxides to 70 atm% or more.
[0006] Although high-nickel positive electrode active materials have the advantage of excellent capacity characteristics, they have a problem of poor life characteristics due to low structural stability, and the crystal lattice structure rapidly deteriorates as charging and discharging proceeds. For this reason, a method is used in which a coating layer is formed on the surface of the positive electrode active material using boron (B) or the like to suppress contact with the electrolyte and improve the structural stability of the high-nickel positive electrode active material. However, in the case of high-nickel positive electrode active materials with a boron coating layer, although the structural stability is improved, the resistance increases and the output characteristics decrease, and especially at low charge states and low temperatures, the output characteristics decrease due to the increase in resistance, making them unsuitable as materials for electric vehicles, which are required to maintain sufficient output even at low charge states and low temperatures.
[0007] Therefore, there is a need for the development of a high-nickel positive electrode active material that is excellent in structural stability and can maintain sufficient output even in a low charged state and at low temperatures. Summary of the Invention [Problem to be solved by the invention]
[0008] The present invention has been made to solve the above-mentioned problems, and has an object to provide a positive electrode active material with improved output characteristics at a low state of charge (SOC) and at low temperatures, and a method for producing the same.
[0009] Another object of the present invention is to provide a positive electrode containing the positive electrode active material and a lithium secondary battery containing the positive electrode. [Means for solving the problem]
[0010] In one aspect, the present invention provides a positive electrode active material including a lithium composite transition metal oxide containing 70 atm % or more of nickel among all metal elements other than lithium, and a coating layer formed on a surface of the lithium composite transition metal oxide and containing Ti and B, the positive electrode active material containing 300 ppm to 800 ppm of Ti and 500 ppm to 1000 ppm of B relative to the total weight of the positive electrode active material.
[0011] In another aspect, the present invention provides a method for producing the above-mentioned positive electrode active material, the method including dry-mixing a lithium transition metal oxide containing 70 atm % or more of nickel among all metal elements other than lithium, a Ti-containing raw material, and a B-containing raw material, followed by heat treatment.
[0012] In still another aspect, the present invention provides a positive electrode comprising the positive electrode active material according to the present invention, and a lithium secondary battery comprising the positive electrode. Effect of the Invention
[0013] The positive electrode active material according to the present invention, which contains Ti and B in specific amounts, can maintain excellent output characteristics at low state of charge (SOC) and low temperature, and can therefore be usefully used in secondary batteries for electric vehicles, which require high output characteristics at low state of charge and low temperature.
[0014] In addition, the method for producing a positive electrode active material according to the present invention has an advantage that since a coating layer is formed by a dry coating method, additional processes such as filtration and drying are not required, and the process is simple, and since there is no need to consider solubility in an organic solvent, there are fewer limitations on coating raw materials.
[0015] In addition, the method for producing a positive electrode active material according to the present invention uses both a Ti-containing raw material and a B-containing raw material when forming a coating layer, so that the coating layer can be formed at a low heat treatment temperature of 300° C. to 500° C. This makes it possible to prevent deformation of the crystal structure of the lithium composite transition metal oxide due to high-temperature heat treatment.
[0016] In addition, according to the method for producing a positive electrode active material according to the present invention, when the coating layer is formed, Ti and B penetrate into the secondary particles, and coating is performed not only on the surface but also on the inside of the lithium composite transition metal oxide, thereby further improving the stability of the positive electrode active material. [Brief description of the drawings]
[0017] [Figure 1] 1 is a graph showing the amount of change in voltage when exposed to low temperatures in lithium secondary batteries using positive electrode active materials prepared according to Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.
[0019] The present invention will be specifically described below.
[0020] positive electrode active material First, the positive electrode active material according to the present invention will be described.
[0021] The positive electrode active material according to the present invention includes a lithium composite transition metal oxide and a coating layer containing Ti and B formed on the surface of the lithium composite transition metal oxide.
[0022] The lithium composite transition metal oxide may be a lithium composite transition metal oxide containing nickel, specifically, a lithium composite transition metal oxide containing 70 atm% or more of nickel among all metal elements other than lithium. When the nickel content in the lithium composite transition metal oxide is 70 atm% or more, the lithium composite transition metal oxide exhibits high capacity and can be usefully applied to high capacity batteries used in electric vehicles and the like.
[0023] Specifically, the lithium transition metal composite oxide may be represented by the following [Chemical Formula 1].
[0024] [Chemical formula 1] Li a [Ni x Co y M 1 Z M 2 w ]O2
[0025] In the above Chemical Formula 1, M 1 can be Mn, Al or a combination thereof, and preferably Mn or a combination of Mn and Al.
[0026] M 2 can be one or more selected from the group consisting of W, Mo, Cr, Zr, Ti, Mg, Ta, Nb, Al, Ce, Hf, La, Sr, and Ba.
[0027] The a represents a molar ratio of lithium to transition metal, and may be 0.8≦a≦1.2, preferably 0.9≦a≦1.1, and more preferably 1.0≦a≦1.1. When a satisfies the above range, the layered crystal structure of the lithium transition metal composite oxide can be well developed.
[0028] The x represents a molar ratio of nickel among metal elements other than lithium, and may be 0.7≦x<1, 0.7≦x≦0.99, or 0.7≦x≦0.98. When x satisfies the above range, excellent capacity characteristics can be achieved.
[0029] The y represents the molar ratio of cobalt among the metal elements other than lithium, and is 0 <y<0.3、0.01<y<0.3または0.01<y≦0.2であることができる。
[0030] The z is M among metal elements other than lithium. 1Indicates the molar ratio of elements, 0 <z<0.3、0.01<z<0.3または0.01<z≦0.2であることができる。
[0031] The w is a doping element M doped into the transition metal layer of the lithium composite transition metal oxide. 2 and may be 0≦w≦0.02 or 0≦w≦0.01.
[0032] The high-nickel lithium composite transition metal oxide, which contains a high concentration of nickel like the lithium composite transition metal oxide, has the advantage of excellent capacity characteristics. 2+ From Ni 3+ Or Ni 4+ Oxygen desorption due to oxidation to lithium composite transition metal oxide occurs rapidly. The desorbed oxygen makes the crystal lattice of the lithium composite transition metal oxide unstable and even causes the collapse of the crystal lattice. In addition, a reaction occurs with the decomposed electrolyte on the surface of the high-nickel lithium composite transition metal oxide, which increases gas generation and resistance. Therefore, the high-nickel lithium composite transition metal oxide has a problem of fragile structural stability. In order to solve this problem, a method has been used in which a boron coating layer is formed on the surface of the lithium composite transition metal oxide to minimize contact with the electrolyte, thereby improving structural stability. However, when a boron coating layer is formed on the surface of the lithium composite transition metal oxide, although structural stability is improved, there is a problem that the resistance increases and output characteristics are reduced, and especially at low charge states and low temperatures, the output characteristics are reduced due to the increase in resistance.
[0033] As a result of intensive research to solve the above problems, the present inventors have found that by forming a coating layer containing Ti and B simultaneously on the surface of a lithium composite transition metal oxide, and by containing Ti and B in specific amounts, it is possible to improve the structural stability of the positive electrode active material and minimize the deterioration of output characteristics at low state of charge and low temperature.
[0034] Specifically, the positive electrode active material according to the present invention includes a coating layer formed on the surface of a lithium composite transition metal oxide and containing Ti and B, and contains Ti in an amount of 300 ppm to 800 ppm, preferably 400 to 700 ppm, and B in an amount of 500 ppm to 1000 ppm, preferably 600 to 900 ppm, based on the total weight of the positive electrode active material. If the contents of Ti and B deviate from the above ranges, there is little improvement in output characteristics at low charge states and low temperatures. Specifically, if the content of Ti is less than 300 ppm, there is almost no improvement in output characteristics, and if it exceeds 800 ppm, there may be problems of reduced discharge capacity and increased gas generation. In addition, if the content of B is less than 500 ppm, there is a problem of reduced discharge capacity characteristics, and if it exceeds 1000 ppm, there is a problem of increased resistance.
[0035] Meanwhile, in the present invention, by adding both B and Ti when forming a coating layer, the melting point of the Ti-containing raw material is lowered, making it possible to form a coating layer by a dry coating method. Since Ti-containing raw materials such as TiO2 have a high melting point, when forming a coating layer by a dry coating method using these raw materials, heat treatment at a high temperature of 700°C or more is required. However, when forming a coating layer, if heat treatment is performed at a high temperature of 700°C or more, there is a problem that the crystal structure of the lithium composite transition metal oxide may be deformed. Therefore, it has been difficult to form a coating layer containing Ti using a dry coating method in the past, and a method of dissolving a Ti raw material in a solvent and then wet coating has been mainly used. However, when using such a wet coating method, a separate process for removing the solvent is required, making the process complicated, and there are problems that the surface characteristics and performance of the lithium composite transition metal oxide may be deteriorated depending on the solvent used in the coating process.
[0036] However, in the case of the present invention where the Ti-containing raw material and the B-containing raw material are mixed together to form a coating layer, the B-containing raw material causes a liquefaction phenomenon at the interface of the Ti-containing raw material, lowering the melting point of the Ti-containing raw material, and the coating layer can be smoothly formed even when heat treatment is performed at a low temperature of about 300 to 500°C.
[0037] Meanwhile, the lithium composite transition metal oxide used in the present invention may be in the form of secondary particles formed by agglomeration of primary particles, and the coating raw material moves to the interface between the primary particles having low surface energy on the surface of the secondary particles of the lithium composite transition metal oxide due to the liquefaction phenomenon, and diffuses into the inside of the secondary particles along the interface of the primary particles during heat treatment. Therefore, in the positive electrode active material according to the present invention, the coating raw materials Ti and B are distributed not only on the surface but also inside the secondary particles of the lithium composite transition metal oxide. In this way, when Ti and B are distributed on the surface and inside of the secondary particles, the interface between the primary particles inside the particles is coated, and the structural stability of the positive electrode active material can be further improved.
[0038] Method for producing positive electrode active material Next, a method for producing the positive electrode active material according to the present invention will be described.
[0039] The method for producing a positive electrode active material according to the present invention includes dry-mixing a lithium composite transition metal oxide containing 70 atm % or more of nickel among all metal elements other than lithium, a Ti-containing raw material, and a B-containing raw material, followed by heat treatment.
[0040] When the nickel content in the lithium composite transition metal oxide is 70 atm % or more, the lithium composite transition metal oxide exhibits high capacity and can therefore be usefully applied to high capacity batteries for use in electric vehicles and the like.
[0041] Specifically, the lithium transition metal composite oxide may be represented by the following [Chemical Formula 1].
[0042] [Chemical formula 1] Lia [Ni x Co y M 1 Z M 2 w ]O2
[0043] In the above Chemical Formula 1, M 1 can be Mn, Al or a combination thereof, and preferably Mn or a combination of Mn and Al.
[0044] M 2 can be one or more selected from the group consisting of W, Mo, Cr, Zr, Ti, Mg, Ta, Nb, Al, Ce, Hf, La, Sr, and Ba.
[0045] The a represents a molar ratio of lithium to transition metal, and may be 0.8≦a≦1.2, preferably 0.9≦a≦1.1, and more preferably 1.0≦a≦1.1. When a satisfies the above range, the layered crystal structure of the lithium transition metal composite oxide can be well developed.
[0046] The x represents a molar ratio of nickel among metal elements other than lithium, and may be 0.7≦x<1, 0.7≦x≦0.99, or 0.7≦x≦0.98. When x satisfies the above range, excellent capacity characteristics can be achieved.
[0047] The y represents the molar ratio of cobalt among the metal elements other than lithium, and is 0 <y<0.3、0.01<y<0.3または0.01<y≦0.2であることができる。
[0048] The z is M among metal elements other than lithium. 1 Indicates the molar ratio of elements, 0 <z<0.3、0.01<z<0.3または0.01<z≦0.2であることができる。
[0049] The w is a doping element M doped into the transition metal layer of the lithium composite transition metal oxide. 2and may be 0≦w≦0.02 or 0≦w≦0.01.
[0050] The Ti-containing source material is, for example, TiO2, TiCl4, TiN, Cl2H 28 Among them, TiO2 is particularly preferred because it is inexpensive, non-toxic and therefore easy to handle.
[0051] The Ti-containing raw material may be mixed in an amount of 0.01 to 0.2 parts by weight, preferably 0.05 to 0.15 parts by weight, and more preferably 0.05 to 0.14 parts by weight, based on 100 parts by weight of the lithium composite transition metal oxide. When the amount of the Ti-containing raw material mixed satisfies the above range, the effect of improving the output characteristics at low charge state and low temperature is excellent, and the decrease in discharge capacity and the increase in resistance and gas generation can be prevented.
[0052] The B-containing raw material is, for example, H3BO3, HB2O3, C6H5B(OH)2, (C6H5O)3B, [CH3(CH2)3O]3B, Cl3H 19 It can be BO3, C3H9B3O6, (C3H7O)3B, etc., and among them, H3BO3 is particularly preferred because it can effectively lower the melting point of TiO2 and has the effect of improving the charge / discharge capacity.
[0053] The B-containing raw material may be mixed in an amount of 0.1 to 1 part by weight, preferably 0.2 to 0.8 parts by weight, more preferably 0.3 to 0.6 parts by weight, based on 100 parts by weight of the lithium composite transition metal oxide. When the content of the B-containing raw material is within the above range, the decrease in discharge capacity and the increase in resistance can be suppressed, and excellent output characteristics are exhibited at a low state of charge and at a low temperature.
[0054] Meanwhile, the lithium composite transition metal oxide, the Ti-containing raw material, and the B-containing raw material are mixed by a dry mixing method. Here, the dry mixing may be performed using a mixer or the like. When the lithium composite transition metal oxide and the coating raw material are dry mixed to form a coating layer as in the present invention, a solvent removal process is not required compared to a wet mixing process, so that not only is the process simpler, but damage to the lithium composite transition metal oxide caused by the solvent can be minimized, and the performance of the lithium composite transition metal oxide can be further improved.
[0055] After the lithium composite transition metal oxide, the Ti-containing raw material, and the B-containing raw material are mixed by dry mixing, a coating layer is formed by heat treatment. At this time, the heat treatment can be performed at a temperature of 300° C. to 500° C., preferably 350° C. to 450° C. If the heat treatment temperature is less than 300° C., the coating layer is not smoothly formed, and if it exceeds 500° C., the physical properties of the lithium composite transition metal oxide may be impaired.
[0056] Since Ti-containing raw materials such as TiO2 have a high melting point, when a coating layer is formed using the Ti-containing raw material alone, a coating layer is not formed when heat treatment is performed at a temperature of 300°C to 500°C. However, when a coating layer is formed by mixing the Ti-containing raw material and the B-containing raw material together as in the present invention, a liquefaction phenomenon occurs at the interface of the Ti-containing raw material due to the B-containing raw material, lowering the melting point of the Ti-containing raw material, and a coating layer can be smoothly formed even when heat treatment is performed at a low temperature of about 300°C to 500°C.
[0057] positive electrode Next, the positive electrode according to the present invention will be described.
[0058] The positive electrode according to the present invention includes the positive electrode active material according to the present invention described above. Since the positive electrode active material has been described above, a detailed description thereof will be omitted, and the remaining components will be described below.
[0059] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector and including the above-mentioned positive electrode active material.
[0060] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can usually have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0061] The positive electrode active material layer may contain a conductive material and a binder in addition to the positive electrode active material.
[0062] Here, the positive electrode active material may be included in an amount of 80 to 99 wt %, more specifically, 85 to 98 wt %, based on the total weight of the positive electrode active material layer, and excellent capacity characteristics can be exhibited when included in the above content range.
[0063] Here, the conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery that is constructed and has electronic conductivity. Specific examples of the conductive material include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these can be used alone or in combination. The conductive material can be contained in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.
[0064] The binder serves to improve the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, and various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 1 to 30% by weight based on the total weight of the positive electrode active material layer.
[0065] The positive electrode can be manufactured according to a conventional positive electrode manufacturing method, except for using the positive electrode active material described above. Specifically, the positive electrode can be manufactured by applying a positive electrode mixture, which is manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent, onto a positive electrode current collector, followed by drying and rolling, or by casting the positive electrode mixture onto another support, peeling it off from the support, and laminating the resulting film onto a positive electrode current collector.
[0066] The solvent used to prepare the positive electrode composite may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity when applied to prepare a positive electrode, taking into consideration the coating thickness of the slurry and the manufacturing yield.
[0067] Lithium secondary battery The positive electrode according to the present invention can be usefully applied to an electrochemical device, for example, a battery, a capacitor, etc., and more specifically, a lithium secondary battery.
[0068] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. In this case, the positive electrode is the positive electrode according to the present invention. Since the positive electrode has been described above, detailed description thereof will be omitted, and only the remaining components will be described in detail below.
[0069] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0070] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0071] The negative electrode active material layer includes a negative electrode active material, and optionally a binder and a conductive material.
[0072] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. Also, a metallic lithium thin film may be used as the negative electrode active material. The negative electrode active material may be included in an amount of 80 wt% to 99 wt% based on the total weight of the negative electrode active material layer.
[0073] The binder is a component that facilitates bonding between the conductive material, the active material, and the current collector, and can usually be included in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.
[0074] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, specifically 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of such conductive materials include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0075] The negative electrode active material layer can be produced by applying a negative electrode mixture, which is prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent, onto a negative electrode current collector and drying the applied mixture. Alternatively, the negative electrode mixture can be cast onto a separate support, and then peeled off from the support to obtain a film, which can be laminated onto the negative electrode current collector.
[0076] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent humidification ability of the electrolyte solution is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, etc., can be used. In addition, a coated separator containing a ceramic component or a polymeric material can be used to ensure heat resistance or mechanical strength, and can be selectively used as a single layer or a multilayer structure.
[0077] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.
[0078] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0079] The organic solvent may be any solvent that can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that can be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can enhance the charge / discharge performance of a battery and a low-viscosity straight-chain carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred.
[0080] The lithium salt can be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably within the range of 0.1 to 4.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.
[0081] In addition to the electrolyte components, the electrolyte may further contain additives for the purposes of improving the life characteristics of the battery, suppressing a decrease in the battery capacity, and improving the discharge capacity of the battery.
[0082] The lithium secondary battery can be usefully used in portable devices such as mobile phones, notebook computers, and digital cameras, as well as in the field of electric vehicles, and is particularly useful as a battery for electric vehicles.
[0083] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof so that those skilled in the art can easily implement the present invention. However, the present invention may be embodied in many different forms and should not be construed as limited to the exemplary embodiments set forth herein.
[0084] Example 1 Li[Ni 0.7 Co 0.1 Mn 0.2 100 g of 1H2O, 0.1 g of TiO, and 0.5 g of H3BO were mixed in a mixer (Acoustic mixer, manufactured by Resodyn) and then heat-treated in an air atmosphere at 370° C. for 7 hours. The heat-treated powder was then crushed in a mortar and classified using a 325 mesh to obtain a positive electrode active material A.
[0085] The Ti and B contents of the obtained positive electrode active material A were 600 ppm and 800 ppm, respectively. Here, the Ti and B contents were analyzed by an ICP (Inductively Coupled Plasma) method.
[0086] Example 2 Li[Ni 0.7 Co 0.1 Mn 0.2 A positive electrode active material B was obtained in the same manner as in Example 1, except that 100 g of ]O2, 0.05 g of TiO2, and 0.3 g of H3BO3 were charged into a mixer and dry mixed.
[0087] The Ti and B contents of the obtained positive electrode active material B were 300 ppm and 500 ppm, respectively.
[0088] Example 3 Li[Ni 0.7 Co 0.1 Mn 0.2 A positive electrode active material C was obtained in the same manner as in Example 1, except that 100 g of ]O2, 0.14 g of TiO2, and 0.6 g of H3BO3 were charged into a mixer and dry mixed.
[0089] The Ti and B contents of the obtained positive electrode active material C were 800 ppm and 1000 ppm, respectively.
[0090] Comparative Example 1 Li[Ni 0.7 Co 0.1 Mn 0.2 A positive electrode active material D was obtained in the same manner as in Example 1, except that 100 g of 1H2O2 and 0.5 g of H3BO3 were charged into a mixer and dry mixed.
[0091] The B content of the obtained positive electrode active material D was 800 ppm.
[0092] Comparative Example 2 Li[Ni 0.7 Co 0.1 Mn 0.2A positive electrode active material E was produced in the same manner as in Example 1, except that 100 g of 1H2O2 and 0.1 g of TiO2 were added to a mixer and dry mixed.
[0093] The Ti content of the obtained positive electrode active material E was 600 ppm.
[0094] Comparative Example 3 Li[Ni 0.7 Co 0.1 Mn 0.2 A positive electrode active material F was obtained in the same manner as in Example 1, except that 100 g of ]O2, 0.03 g of TiO2, and 0.5 g of H3BO3 were charged into a mixer and dry mixed.
[0095] The Ti and B contents of the obtained positive electrode active material F were 200 ppm and 800 ppm, respectively.
[0096] Comparative Example 4 Li[Ni 0.7 Co 0.1 Mn 0.2 A positive electrode active material G was obtained in the same manner as in Example 1, except that 100 g of ]O2, 0.17 g of TiO2, and 0.5 g of H3BO3 were charged into a mixer and dry mixed.
[0097] The Ti and B contents of the obtained positive electrode active material G were 1000 ppm and 800 ppm, respectively.
[0098] Comparative Example 5 Li[Ni 0.7 Co 0.1 Mn 0.2 A positive electrode active material H was obtained in the same manner as in Example 1, except that 100 g of ]O2, 0.1 g of TiO2, and 0.24 g of H3BO3 were charged into a mixer and dry mixed.
[0099] The Ti and B contents of the obtained positive electrode active material H were 600 ppm and 400 ppm, respectively.
[0100] Comparative Example 6 Li[Ni 0.7 Co 0.1 Mn 0.2A positive electrode active material I was obtained in the same manner as in Example 1, except that 100 g of ]O2, 0.1 g of TiO2, and 0.66 g of H3BO3 were charged into a mixer and dry mixed.
[0101] The Ti and B contents of the obtained positive electrode active material I were 600 ppm and 1100 ppm, respectively.
[0102] Experimental Example The positive electrode active materials prepared in Examples 1 to 3 and Comparative Examples 1 to 6, carbon black conductive material, and PVDF binder were mixed in a weight ratio of 96.5:1.5:2 in N-methyl-2-pyrrolidone (NMP) to prepare positive electrode mixtures. The positive electrode mixtures were coated on aluminum current collectors, dried, and then rolled to prepare positive electrodes.
[0103] Anode active material (a mixture of natural graphite and artificial graphite in a weight ratio of 1:1), carbon black, and binder (BML302, Zeon) were mixed in N-methyl-2-pyrrolidone (NMP) in a weight ratio of 96:1:3 to prepare anode composite. The anode composite was coated on a copper current collector, dried, and then rolled to prepare anode.
[0104] A polyethylene separator was interposed between the positive and negative electrodes to prepare an electrode assembly, and an electrolyte was injected to prepare a lithium secondary battery. The electrolyte was a solution of LiPF6 dissolved at a concentration of 1M in an organic solvent in which ethylene carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) was mixed in a volume ratio of 3:4:3.
[0105] The output characteristics at SOC 10% and low temperature output characteristics of the secondary battery prepared as above were measured as follows.
[0106] (1) Output characteristics at SOC 10%: The secondary battery prepared above was charged to SOC 10% at room temperature (25° C.), and then the resistance was measured for 10 seconds while discharging. The measurement results are shown in Table 1 below. (2) Low-temperature output characteristics: The secondary battery prepared above was charged to SOC 20% at room temperature (25°C), and then the charged secondary battery was discharged to 3V at 0.6C in a chamber at -25°C, and the change in voltage over time was measured. The measurement results are shown in Figure 1.
[0107] [Table 1]
[0108] Referring to Table 1, it can be seen that the lithium secondary batteries using the positive electrode active materials of Examples 1 to 3 containing 300 ppm to 800 ppm of Ti and 500 ppm to 1000 ppm of B exhibit lower resistance at a low charged state of SOC 10% and thus have higher output characteristics, compared to the lithium secondary batteries using the positive electrode active materials of Comparative Examples 1 to 6. Specifically, the lithium secondary batteries using the positive electrode active materials of Examples 1 to 3 showed a 3% to 16% decrease in resistance at SOC 10% compared to the lithium secondary batteries using the positive electrode active materials of Comparative Examples 1 to 6.
[0109] 1, it can be seen that the secondary batteries using the positive electrode active materials of Examples 1 to 3 have a smaller voltage change even when exposed to low temperatures, compared to the secondary batteries using the positive electrode active materials of Comparative Examples 1 to 6. That is, when using a positive electrode active material containing 300 ppm to 800 ppm of Ti and 500 ppm to 1000 ppm of B as in the present invention, the voltage change (voltage drop) is small at low temperatures, and therefore the resistance increase is small, resulting in excellent output characteristics.
Claims
1. A lithium composite transition metal oxide containing 70 atm % or more of nickel among all metal elements other than lithium; A positive electrode active material comprising: a coating layer formed on a surface of the lithium composite transition metal oxide and containing Ti and B, The positive electrode active material contains Ti in an amount of 300 ppm to 800 ppm and B in an amount of 500 ppm to 1000 ppm based on the total weight of the positive electrode active material, The lithium transition metal composite oxide is in the form of secondary particles formed by aggregation of primary particles, The Ti is distributed on the surface and inside of the secondary particles of the lithium composite transition metal oxide.
2. 2. The positive electrode active material according to claim 1, comprising Ti in an amount of 400 ppm to 700 ppm and B in an amount of 600 ppm to 900 ppm based on the total weight of the positive electrode active material.
3. The lithium composite transition metal oxide is represented by the following Chemical Formula 1: [Chemical formula 1] Li a [Ni x Co y M 1 Z M 2 w ]O 2 In the above Chemical Formula 1, M 1 is Mn, Al or a combination thereof; M 2 is one or more selected from the group consisting of W, Mo, Cr, Zr, Ti, Mg, Ta and Nb; 2. The positive electrode active material according to claim 1, wherein 0.9≦a≦1.1, 0.7≦x<1, 0<y<0.3, 0<z<0.3, and 0≦w≦0.
02.
4. A method for producing the positive electrode active material according to claim 1, comprising the steps of: A method for producing a positive electrode active material includes a step of dry-mixing a lithium composite transition metal oxide containing 70 atm % or more of nickel among all metal elements other than lithium, a Ti-containing raw material, and a B-containing raw material, and then performing a heat treatment at a temperature of 300°C to 500°C.
5. The Ti-containing raw material is TiO 2 The method for producing a positive electrode active material according to claim 4 ,
6. The B-containing raw material is H 3 B.O. 3 The method for producing a positive electrode active material according to claim 4 ,
7. The method for producing a positive electrode active material according to claim 4, wherein the Ti-containing raw material is mixed in an amount of 0.01 to 0.2 parts by weight based on 100 parts by weight of the lithium composite transition metal oxide.
8. The method for producing a positive electrode active material according to claim 4, wherein the B-containing raw material is mixed in an amount of 0.1 to 1 part by weight based on 100 parts by weight of the lithium composite transition metal oxide.
9. The lithium composite transition metal oxide is represented by the following Chemical Formula 1: [Chemical formula 1] Li a [Ni x Co y M 1 Z M 2 w ]O 2 In the above Chemical Formula 1, M 1 is Mn, Al or a combination thereof; M 2 is one or more selected from the group consisting of W, Mo, Cr, Zr, Ti, Mg, Ta and Nb; The method for producing a positive electrode active material according to claim 4, wherein 0.9≦a≦1.1, 0.7≦x<1, 0<y<0.3, 0<z<0.3, and 0≦w≦0.
02.
10. A positive electrode comprising the positive electrode active material according to claim 1 .
11. A lithium secondary battery comprising: the positive electrode according to claim 10; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte.
Citation Information
Patent Citations
Method for manufacturing positive electrode active material for secondary battery and apparatus for manufacturing active material for secondary battery
JP2020514971A